Fracture fixation in the polytrauma patient: Markers that matter. (May 2020) - Moore, Timothy A.; Simske, Natasha M.; Vallier, Heather A.
Highlights: Reduction and fixation of axial and femoral fractures provides stability and pain relief and promotes mobility from bed. However, definitive fixation should only be undertaken in patients who are hemodynamically and medically stable. Damage control orthopaedics is reserved for the others. Early Appropriate Care describes expeditious definitive management of said fractures once acidosis has improved; EAC has been shown to reduce complications, length of stay and costs. Abstract: Timing and type of fracture fixation in the multiply-injured trauma patient have been important and controversial topics. Ideal care for these patients come from providers who communicate well with one another in a team fashion and view the whole person, rather than focusing on injury to individual systems. This group encompasses a wide range of musculoskeletal and other injuries, further complicated by the broad spectrum of patients, with variability in age, medical and social comorbidities, all of which may have profound impact upon outcomes. The concept of Early Total Care arose from the realization that early definitive fixation of femur fractures provided pulmonary and systemic benefits to most patients. However, insufficient assessment and understanding of the physiological status of polytraumatized patients at the time of major orthopaedic procedures, potentially with inclusion of multiple other procedures in the same setting resulted in more morbidity, swinging the pendulum of care toward initial Damage Control Orthopaedics to minimize surgical insult. More recently, iterative assessment of response to resuscitation using Early Appropriate Care guidelines, suggests definitive fixation of most axial and femoral injuries within 36 h after injury appears safe in resuscitated patients, as measured by improvement of acidosis.